Letter (copy) : Homes for Spanish orphans - Tewson, Vincent
030-0090-001 Secretary's. HVT/FC/602. 17th August, 1938. Mr. E. Edwards, The Mineworkers' Federation of Great Britain, 50, Russell Square, W.C.1. Dear Mr. Edwards, HOMES FOR SPANISH ORPHANS. Further to my telephone conversation with you today I am enclosing copy of a letter which I have sent to Mr. Stoltz. You will notice that on the strength of the assurances received from you on the telephone I state on page 2 that there will be no difficulty in advancing money in respect of the equipment for two Homes and food and clothing for the first three months. In regard to the P.S. nothing specific has been decided on the question of representation, but I was anxious to say something which would stake out a claim for the Mineworkers' Federation in any negotiations which take place with the Spanish Government in respect of the establishment of the Homes. I will not fail to keep you informed of what transpires. Yours sincerely, Assistant Secretary. 292/946/30/90